Associations Between Dopamine Beta-Hydroxylase Gene Polymorphisms and Restless Legs Syndrome: A Case-Control Study - Algul, Fatma Ebru; Tatli, Sinan; Yesilada, Elif (Int Scientific Information, Inc, 2025)
Background: Restless legs syndrome (RLS) is a chronic condition that affects movement and sensation, making it one of the most common nerve-related disorders. Single-gene polymorphisms (SNP) that alter the expression of the dopamine beta-hydroxylase (DBH) enzyme gene, which converts dopamine to noradrenaline, also appear to affect the disease. In this study we investigated the relationship between polymorphisms in DBH gene SNPs (rs129882, rs161115, and rs732833) and the susceptibility to RLS among the Turkish population. Material/Methods: This prospective, case-control study included 103 Turkish patients with RLS and 100 healthy individuals of similar age. The study included RLS patients who met the criteria set by the International RLS Study Group (IRLSSG). DNA was extracted from blood samples taken from the participants, and all cases and controls were genotyped. Results: We found the rs732833 DBH CT and homozygous TT genotype frequency was significantly different between the patient and control groups (P<0.05). Patients with mild disease severity showed a statistically significant variation between C and T alleles of rs1611115 DBH (P=0.008). The C allele is more associated with mild severity compared to the T allele. Conclusions: We showed that the rs732833 DBH polymorphism predisposes individuals to RLS and mild disease severity is more commonly associated with the C allele of rs1611115 DBH than with the T allele. To the best of our knowledge, this is the first study investigating the relationship between RLS and DBH gene polymorphisms.
Keywords: Dopamine beta-Hydroxylase; Polymorphism; Single Nucleotide; Restless Legs Syndrome